Modelling the impact of taxes and wealth increments on labour supply; Modelización del impacto de los impuestos y los incrementos de capital en la oferta laboral - Antonio Pe\~na Pe\~na (Atlantic Review of Economics (ARoEc), 2023)
This paper presents a comprehensive work-leisure model designed to examine the impact of wealth changes on work supply. By incorporating both monetary and non-monetary costs, as well as financial and non-financial benefits, the model conducts a thorough cost-benefit analysis, enabling individuals to choose activities that yield the highest remuneration. The theoretical analysis reveals that taxes have a relatively minor effect on individuals within lower income brackets or levels, but their impact grows exponentially as agents accumulate more capital. Consequently, the loss of efficiency resulting from taxes is significantly greater in higher income brackets compared to lower ones. Moreover, considering the diminishing marginal utility of monetary units, a higher standard of living, ceteris paribus, tends to correspond to a reduction in the number of hours worked. Overall, this research provides valuable insights into the relationship between wealth changes, taxation, and workers' labour supply decisions, contributing to a deeper understanding of economic behaviour and decision-making.
Keywords: D7; H21; J21; 330; cost-benefit analysis; efficiency loss; hours worked; productivity; taxes